The Essential Oil Composition of Arctium lappa Root and Leaf: Essential oil Composition of Arctium lappa Root and Leaf - Golbaz, fariba; Mojab, Faraz; Zarei, Shayesteh; Garakani, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2018)
Using plants and natural products as medicine is increasing every day. The reason might be a tendency that the societies mostly have toward natural and original products especially natural drugs. Essential oils are referred to aromatic composition found in different parts of a plant and can be used for different remedial and hygienic purposes. One of the plants which have been used a lot in folk medicine is Arctium lappa. This study is aimed at identifying the composition of its root and leaf essential oils. The essential oils from the roots and leaves of A. lappa (Asteraceae), collected from Mashhad (Farms of Agriculture School, Ferdowsi University), were extracted by hydrodistillation and then the composition was determined by GC/MS. Totally, 31 and 57 components (92.4 and 93.2% of essential oils of root and leaf) were identified, respectively. The root oil contains mainly 1, 3 cyclo-octadiene (33.2%), E-caryophllene (6.8%), β-selinene (5.6%) and 9, 10-dehydro-isolongifolene (5.5%), whilst β-thujone (11.6%), caryophyllene oxide (8.3%), cuminaldehyde (7.7%), comphor (5.3%), dihydroEdulan II (5.3%), β -ionone (4.7%), and α- Thujone (3.4%) were major components in the leaf oil. Identification of the components was based on comparison of their mass spectra with standards. The chemical composition of essential oils from the herbs is being reported for the first time in Iran.